Combined cognitive and motor training improves the outcome in the early phase after stroke and prevents a decline of executive functions: A pilot study. - Eschweiler, Mareike; Bohr, Lara; Kessler, Josef; Fink, Gereon R.; Kalbe, Elke; Onur, Oezguer A. (NeuroRehabilitation, 2021)
BACKGROUND: The negative impact of cognitive dysfunction on motor rehabilitation as a relearning-process is well known in stroke patients. However, evidence for combined cognitive and motor training (CMT) is lacking. OBJECTIVE: To evaluate the effects of combined CMT in early stroke rehabilitation. METHODS: In a controlled pilot study, 29 moderately affected stroke patients with low-level motor performance and cognitive impairment received motor therapy plus either cognitive (experimental group, EG) or low-frequency ergometer training (control group, CG) for eight days. RESULTS: Both groups improved their motor functioning significantly. After training, between-group comparison revealed significant differences for cognitive flexibility and trends for set-shifting, working memory, and reaction control in favor of the EG. Within-group effects showed improvement across all cognitive domains in the EG, which correlated with gains in bed-mobility, while the CG showed no significant improvement in cognition. Rather, a trend towards reaction control decline was observed, which correlated with less functional progression and recovery. Furthermore, a decline in cognitive flexibility, set-shifting, and working memory was descriptively observed. CONCLUSIONS: Combined CMT may enhance cognition and motor relearning early after stroke and is superior to single motor training. Further studies are needed to replicate these results and investigate long-term benefits.